(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Diabetic nephropathy (DN) also called diabetic kidney disease (DKD) is one of the maincomplications of diabetes mellitus (DM) and it is the most common cause of end-stage renal disease(ESRD). Diabetes mellitus has been proved as conventional risk factors for the development of coronaryartery diseases (CAD). Adipose tissue is now considered as an active endocrine gland secretes severalinflammatory cytokines, namely, adipokines or adipocytokines such as chemerin, visfatin, leptin andothers, which interfere with insulin sensitivity, with glucose and lipid metabolism, and with theinflammatory process. Aim: The aim of this study was to evaluate serum chemerin level and otherbiochemical parameters in in diabetic hemodialized patients to determine the risk of cardiovasculardiseases (CVD) in DKD. Materials and methods: This case control study was conducted on a samplecomposed of 50 patients with diabetic nephropathy and a control group consists of 50 apparently normalhealthy subjects. Estimation of serum chemerin level by ELIZA, lipid profile, Blood urea, serumcreatinine, serum albumin, serum electrolytes, serum uric acid and serum malondialdehyde (MDA) weredone for both patients and control. Body mass index (BMI) and glomerular filtration rate (GFR) werecalculated for both patients and control. Atherogenic index of plasma (AIP) and coronary artery diseaserisk percentage (CAD risk %) were also calculated for both patients and control group. Results: Theresults of this study showed that the level of serum chemerin was significantly higher in DN patientscompared to control.Serum chemerin level was correlated with other parameters.